2015
DOI: 10.1021/acs.energyfuels.5b00964
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Sorption and Desorption of Propylene on Polish Hard Coals

Abstract: Propylene is the unsaturated hydrocarbon emitted to the atmosphere of a coal mine in the process of coal selfheating. Its concentration in mine air is one of the indicators for the assessment of the development of the process of coal selfheating. Coal sorption capacities with respect to propylene may be the reason for the decrease in its concentration in mine air. This may affect the accuracy of the assessment of the self-heating process development, in particular, in the case of coals of considerable sorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The lowest volumes of propylene were sorbed on coal samples 6 and 7, characterized by the lowest porosity and low micropore surface area (see Table 2). The grade of metamorphism [25][26][27], porosity, and chemical characteristics of coal surface [10,11] are the most important properties of coals in terms of their sorption characteristics. The increase in the grade of metamorphism and decrease in coal porosity resulted in the deterioration of sorption capacity of tested coals with respect to propylene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest volumes of propylene were sorbed on coal samples 6 and 7, characterized by the lowest porosity and low micropore surface area (see Table 2). The grade of metamorphism [25][26][27], porosity, and chemical characteristics of coal surface [10,11] are the most important properties of coals in terms of their sorption characteristics. The increase in the grade of metamorphism and decrease in coal porosity resulted in the deterioration of sorption capacity of tested coals with respect to propylene.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the grade of metamorphism and decrease in coal porosity resulted in the deterioration of sorption capacity of tested coals with respect to propylene. The electrostatic interactions between oxygen-containing reactive centers on coal surface and π electrons of the double bonds between carbon atoms play also a significant role in sorption of unsaturated hydrocarbons on coals [9,10,28,29]. Coals of higher oxygen and moisture content, and therefore of higher number of reactive oxygen-containing groups, tended to sorb higher volumes of propylene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of sorption research on hard coal presented in literature is performed on powder samples or on samples of granulation not higher than 0,9mm. As a result of such drastic fragmentation lost of primary pore structure can be observed as well as lost of chemical character of outer coal grains surface, which can have influence on higher values of sorbed amount of gas/vapors [20,21]. In order to characterize the research material there were analysis carried out: porosimetry and densimetry analysis, helium density measurements.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…The study found that the sorption isotherms of hydrocarbon vapors on hard coal in the investigated pressures ranges and temperatures were irreversible, in each of examined cases open hysteresis loop was easily visible (the predominance of sorption processes in the microporous coal structure) [20,21].…”
mentioning
confidence: 93%